"Look Before You Leap": Lessons from Urban Water Sector Reforms in Ghana. (December 2015) - Zaato, Joshua Jebuntie
The article is primarily a case study of the use of a management contract for the reform of urban water in Ghana and addresses two main questions: (1) is contractualism suitable for the reform of urban water sector activities in developing countries; (2) under what conditions can contracting actually promote efficiency in the water sector? The findings point to answers for both questions. First, contractualism is a defective tool for reforming the politically sensitive water sector. Second, in order for contractualism to actually promote efficiency, certain fundamental conditions − context, agency task specificity and creative adaptation − must be adequately addressed.